Borrowing Absolute and Relative Gains to Science Diplomacy Conceptualization - Anshori, Muhammad Fikry; Effendi, Mutiara Rachmadini (Intermestic: Journal of International Studies, 2024)
Science diplomacy is an emerging concept in International Relations. But the existing traditional conceptualization of science diplomacy (science in diplomacy, diplomacy for science, and science for diplomacy) has optimistic scope and objective while ignoring the conflictual nature of international relations. This article argues borrowing relative and absolute gains can address the conceptual problem of science diplomacy. The borrowing presents a classification of science diplomacy into two types, prospective (using diplomacy to attain the maximum individual payoffs in science) and restrictive (using diplomacy to hinder others from advancing capabilities in science). By demonstrating it with Japan's science diplomacy in the inaugural meeting of Science and Technology in Society (STS) Forum and the first meeting of the East Asia Science and Innovation Area (e-ASIA) Joint Research Forum, this article found that the classification of science diplomacy as prospective and restrictive helps study the cooperative and competitive aspects of state actors' science diplomacy.